Faktor-Faktor Yang Mempengaruhi Kegagalan Terapi Pasien TB Paru di Puskesmas Labuan Bajo - Mei, Fransiska Oktaviana; Parthasutema, Ida Ayu Manik; Wintariani, Ni Putu (Bali International University, 2020)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Unsuccessful treatment can be canceled from TB treatment and cessation treatment by patients for certain reasons. Failure of TB therapy can help by several factors such as drug side effects, the level of knowledge of the patient, relationship to taking medication and drug interactions. Purpose: to determine the factors that influence the failure of therapy for pulmonary TB patients at the Labuan Bajo primary health center. Method: This type of research is an observational study with cross sectional research design. The sample in this study were patients who had failed TB treatment therapy as many as 22 patients and patients recovered as many as 13 people in the Labuan Bajo primary health care during 2018 taken by the total sampling technique. The analytical method used is the associative hypothesis correlation coefficient contingency test.. Result: the contingency coefficient correlation test between the knowledge level of TB patients with TB therapy failure (p-value = 0.003 <0.05) showed there was a relationship between the level of knowledge and failure of therapy, adherence to TB patients with TB therapy failure (p-value = 0.001 <0.05) showed an association between adherence to treatment failure, drug side effects with failure of TB therapy (p-value = 0.392> 0.05) showing no association between side effects and failure of therapy, and drug interactions with treatment failure ( (p-value = 0.006 <0.05) shows there is a relationship between drug interactions with failure of therapy. Conclusion: Knowledge, compliance with TB patients and the presence of drug interactions are factors the failure of therapy for TB, while the side effects of drugs do not affect the nervousness of TB patient therapy in the Labuan Bajo health center.